2022
DOI: 10.2147/prbm.s359382
|View full text |Cite
|
Sign up to set email alerts
|

The Benefits of Self-Compassion in Mental Health Professionals: A Systematic Review of Empirical Research

Abstract: The importance of cultivating self-compassion is an often neglected issue among mental health professionals despite the risks to occupational well-being present in psychological care, such as burnout or compassion fatigue. In this context, this literature review has a twofold aim. Firstly, to contribute to raising awareness of the benefits of self-compassion among professionals, based on empirical research findings. Secondly, to coherently organize the available evidence on this topic, which to date appears sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 67 publications
0
1
0
Order By: Relevance
“…There is sufficient evidence that suggests self-compassion interventions to be effective for several mental health conditions such as stress, anxiety, and depression [85,[109][110][111][112], post-traumatic stress disorder (PTSD) [113,114], and suicidal ideation [115]. To date, no review specifically focusing on the role of the media and self-compassion in enhancing mental health and suicide prevention among Nigerian youth has been conducted.…”
Section: Discussionmentioning
confidence: 99%
“…There is sufficient evidence that suggests self-compassion interventions to be effective for several mental health conditions such as stress, anxiety, and depression [85,[109][110][111][112], post-traumatic stress disorder (PTSD) [113,114], and suicidal ideation [115]. To date, no review specifically focusing on the role of the media and self-compassion in enhancing mental health and suicide prevention among Nigerian youth has been conducted.…”
Section: Discussionmentioning
confidence: 99%
“…Hong Kong Annual Reports (2021–2022) indicated that the absence of face-to-face interaction and limited opportunities for real-time feedback led to decreased student engagement, ultimately affecting teaching performance. Research illustrates that individuals high in self-compassion report greater emotional wellbeing that may improve the job performance because it protects individuals from social stressors through engaging in self-kindness and learning to accept that having imperfections is part of human nature (Crego et al , 2022). In this context, research on malleable factors that can improve teacher job performance is desirable.…”
Section: Introductionmentioning
confidence: 99%
“…Current evidence includes only a few systematic reviews in the field of compassion fatigue [46][47][48][49][50][51][52]. These reviews have significant heterogeneity in the participant (e.g., physicians, nurses, radiographers), faculty (e.g., oncology, emergency department), and location (e.g., rural, low-middle income nations) characteristics, and the evaluated aspects of compassion fatigue (e.g., prevalence, risk factors, interventions).…”
Section: Introductionmentioning
confidence: 99%